PLANT COMMUNITIES DETERMINED BY CLIMATE AND SOIL PARAMETERS ALONG AN ALTITUDINAL GRADIENT IN THE CHANCHAMAYO VALLEY, PERU - REYES GRANDE, Carlo Eduardo (2024)
Understanding the factors that determine the distribution of plant communities allows us to identify how climate and soil gradients influence the presence and abundance of species. In this paper, environmental parameters that determine species distribution along an altitudinal gradient were identified in the Chanchamayo valley. Using ordination and classification techniques, twelve 1 ha permanent plots were analyzed according to species affinities with climate and soil parameters. The results revealed three distinct plant communities, primarily governed by altitude (m), solar radiation (kJ m⁻² day⁻¹), and exchangeable acidity (Al³⁺H⁺, meq/100 g). This pattern confirms that, at more local scales, topographic and edaphic factors are determining factors in species assembly.